Implementasi Peran Mahasiswa dalam Kegiatan Pembelajaran Anak Usia Dini dan Keagamaan di Lingkungan Masyarakat: Implementation of the Role of Students in Early Childhood Learning and Religious Activities in the Community Environment - Salsabila Tarivita Putri; Shandy Muslikah Zulfa; Faiza Athaya Wahyu Putri; Amanda Argi Sevia; Dwi Puspitasari; Dyandra Pramitha Kundera; Ellena Prima Hapsari (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This community service activity aims to improve the quality of learning and religious guidance in early childhood through the implementation of activities at Aisyiyah Kindergarten, Mentoring at TPQ Al-Kautsar Mosque, and participating in routine recitation with the community in Pabelan, Kartasura. The methods applied are educational and participatory with an interactive approach, such as coloring activities, playing while learning, storytelling, guidance in reading the Koran and memorizing short letters. The results of this activity show an increase in children's creativity and enthusiasm for children's involvement in the learning process so as to create a more active and conducive learning atmosphere and interest in religious activities. In addition to having a positive impact on the community, this activity also provides direct experience for students in implementing religious values, building character and fostering social care. It can be concluded that this community service activity succeeded in creating positive changes in the management of education in Aisyiyah Kindergarten and TPQ, and made a valuable contribution to routine recitation activities.